(untitled) (Global Journal of Human-Social Science, 2020)
This research is based on the main problem regarding the community around the Forest Education and Training (ET).Generally, They do not only fully understand but also they have no sense of belonging , realize the importance of forests and forestry for human life and other living things. The community is one of the factors that causing disruption on forest areas and forest products, theft, forest fires, forests are used as landfills, and the economic conditions of the middle to lower classes, this can cause damage the Forest Education and Training area. The purpose of this research is to find out and illustrate more deeply about how the strategy build the community organization of forest management, then gaining the steps that can be obtained more effective and efficient so that community organizations are sustainable, and increase with the changing times, so that it is expected to be a solution to the problem solving that occurs towards Forest Education and Training.